Magneto and Magneto-Optical Characteristics of Semiconductor Nano Material with Nonsymmetrical Geometry (Bulletin of Pure and Applied Sciences – Physics, 2020)
We have studied and calculated the diamagnetic coefficient for the neutral excitons  confined in wobbled semiconductor self assembled quantum rings. We have  systematically studied the impact of the rings reflection asymmetry on the excitons  ground-state wave function localization, energy and diamagnetic coefficient. Using  mapping method, we have reproduced three dimensional geometrical shapes and  material compositions of the rings and simulated excitonic properties of the rings  with the reflection symmetry and when the symmetry was broken. We have  demonstrated that for the rings with reflection symmetry with respect to reflection in  (110) plane Y-Z, the ground state excitons wave function is equally distributed  between two potential valley of the rings. A small imbalance in geometrical or  material characteristics of rings along the (110) direction of x-axis leaded to the  localization of the potential valleys of the ring, which caused a significant decrease  of the excitons diamagnetic coefficient. We have found that for the noninteracting  particles, the electron wave function is more stable to the unbalance in the ring  reflection symmetry than the hole wave function. This originates from the difference  in the particles effective masses. The effective lateral radii of the electron and hole  are shrinking rapidly when absolute values of the parameters are growing. This  resulted in the rapid decrease of the neutral excitons diamagnetic coefficient. We  have also found that a correlation imbalance in the ring geometry and material  content has a recognizable impact on the ground state energy of the neutral excitons.  The obtained results were found in good agreement with previously obtained  results.